Advances in G protein-coupled receptor high-throughput screening. (August 2020) - Yasi, Emily A.; Kruyer, Nicholas S.; Peralta-Yahya, Pamela
Abstract : G protein-coupled receptors (GPCRs) detect compounds on the cell surface and are the starting point of a number of medically relevant signaling cascades. Indeed, over 30% of FDA approved drugs target GPCRs, making them a primary target for drug discovery. Computational and experimental high-throughput screening (HTS) approaches of clinically relevant GPCRs are a first-line drug discovery effort in biomedical research. In this opinion, we review recent advances in GPCR HTS. We focus primarily on cell-based assays, and highlight recent advances in in vitro assays using purified receptors, and computational approaches for GPCR HTS. To date, GPCR HTS has led to the identification of new and repurposing of existing drugs, and the deorphanization of GPCRs with unknown ligands. As automation equipment becomes more common, GPCR HTS will move beyond a drug discovery tool to a key technology to probe basic biological processes that will have an outsized impact on personalized medicine.